Evaluating the Vocabulary Coverage of EFL Textbooks and Teachers’ Generated Materials in an Indonesian Islamic Universities:A Corpus-Informed Materials Evaluation - Srifani Simbuka (AL-ISHLAH: Jurnal Pendidikan, 2021)
The importance of vocabulary in the learning of EFL has been an indisputable matter in ELT. The inclusion of vocabulary in ELT materials is often accompanied with questions such as what type of vocabulary and how many words to be taught for students in diverse ELT contexts. Hence, evaluating the kinds of vocabulary in ELT materials is similarly important. This study demonstrates a considerably unconventional corpus -informed materials evaluation to assess the suitability of the vocabulary content of ELT course books taught at the State Islamic Institute in Manado with its ESP context. Four ELT course books taught at the four schools of the State Islamic Institute were analysed using the corpus-based methods. A special software designed for corpus linguistics studies called e Antwordprofiler was used to count the coverage/frequency of occurrence of three types of Nation’ vocabulary classification. The results showed that the examined course books contain sufficient coverage of English high frequency words as required by theory that they contain a total coverage of 84.14 % of high frequency English word enlisted in the General Service List (GSL). However, in terms of the coverage of academic and technical vocabulary, these course books content were still considered under the theoretically acceptable coverage of at least 12,4 % and 5 % respectively. It is recommended that for ELT course books that are used in ESP teaching such as in a field-specific Islamic studies programs, the course books should fulfil the minimum coverage threshold of high frequency, academic and technical vocabulary.